Exploring the clinical significance of anti-acetylcholine receptor antibody titers, changes, and change rates in Myasthenia Gravis - Lijun Luo; Xinyi Zhu; Chunbei Wen; Yifan Guo; Jie Yang; Dongsheng Wei; Ping Yu; Mei Wan (Frontiers in Neurology)
Introduction/AimsMyasthenia Gravis (MG) is a common neuromuscular junction disorder that is primarily mediated by anti-acetylcholine receptor antibodies (AChR-Ab). However, using AChR-Ab titers to predict MG severity and improvement remains controversial. This study aims to explore the relationship between AChR-Ab titers and AChR-Ab rate of change (RR-AChR-Ab, %) and MG scores.MethodsWe used a prospective study approach, and included 62 patients with generalized MG (GMG) who were positive for AChR-Ab. We measured AChR-Ab titers, MGFA-QMGS, and MG-ADL scores at baseline (before treatment) and at 3 and 6 months into treatment. Pearson and Spearman correlation analyses were used to study the relationships between changes in AChR-Ab titers, rates of change, and MG scores.Results(1) At baseline, there was no correlation between AChR-Ab titers and age, duration of illness, gender, MGFA classification, or presence of thymic abnormalities. (2) The trend of decreasing AChR-Ab titers matched the trend of reduced QMGS and ADL scores. (3) Six months into treatment,there was a correlation between AChR-Ab titer changes and changes in ADL scores. (4) Three months into treatment, RR-AChRAb showed a correlation with the rate of change in ADL at the same time point.ConclusionWe found the trend of decreased AChR-Ab titers after standardized treatment that was consistent with reductions in QMGS and ADL scores. Additionally, the rate of change in AChR-Ab titers at 3 months and the change in AChR-Ab titers at 6 months into treatment did reflect improvements in activities of daily living for MG patients.